Tornar-se professora: narrativa e caminhos formativos em licenciatura em pedagogia - Marques, Neila dos Anjos (Brasil, 2024)
This Course Conclusion Work aims to narrate the life story of student Neila dos Anjos Marques, her trajectory and educational path throughout the pedagogy course, bringing reflections both as an academic and as an education professional. Furthermore, it presents the difficulties and possibilities faced throughout the academic career, the challenges overcome in the process of becoming a literacy teacher and the discoveries along the way, highlighting, above all, the commitment to education.